دور المسجد في مكافحة الآفات الاجتماعية ( دراسة ميدانية على عينة من طلبة جامعة الوادي) - تواتي, عايدة; قعري, سليمة (University of Eloued جامعة الوادي, 2020)
"هذه الدراسة محاولة لتسليط الضوء على دور المسجد في مكافحة الآفات الاجتماعية ويتلخص مضمون الدراسة في: مقدمة وخمسة فصول وخاتمة، وقد تمت معالجة وبحث الموضوع من خلال المخطط الآتي: فصل تمهيدي واشتمل على الإطار التصوري للدراسة وفيه تم تحديد الإشكالية وتساؤلاتها وبيان أهمية وأهداف الموضوع، والوقوف على الدراسات السابقة وتحديد مصطلحات الدراسة. وتضمن الفصل الثاني الخاص بماهية المسجد بدءا بلمحة تاريخية عن نشأة المسجد وبيان فضل بنائه وعمارته في القرآن الكريم ثم تطرق إلى أنواعه وأهميته وأهدافه وبيان وظائفه ثم الكشف عن دوره في بناء الجماعة الإسلامية وصولا إلى مكانة الإسلام. الفصل الثالث خاص بموضوع الآفات الاجتماعية وذكر بعض منها من خلال تعريفها والإشارة إلى حكم الشرع فيها وبيان دور المسجد في مكافحتها. وفي الفصل الرابع الخاص بالإطار المنهجي للدراسة اشتمل على مجالات الدراسة وبيان المنهج المستخدم في الدراسة وأدوات جمع البيانات ومجتمع البحث والعينة ثم الخلفية النظرية للدراسة. والفصل الخامس تمت فيه معالجة الموضوع في إطاره الميداني حيث تم عرض وتحليل نتائج الدراسة الميدانية. وفي خاتمة الدراسة توصلنا إلى نتائج من أهمها: - يعتبر المسجد من أهم قواعد المجتمع الإسلامي لكونه ملتقى للمسلمين لدراسة أحوالهم الاجتماعية. - خطورة تعاطي المخدرات على صحة الفرد مما يؤدي به إلى العجز الدائم والهلاك. - يعتبر غياب الوازع الديني من أهم أسباب انتشار الآفات الاجتماعية في المجتمع الإسلامي. - يحتل المسجد مكانة سامية كونه اللسان المعاصر لرسالة الإسلام. - تشير نتائج الدراسة من إجابات الطلاب إلى غياب الدور الوقائي الفعال حول الآفات الاجتماعية من كل جوانبها. "this study is anattempt to sesed light on role of the mosque the content of the study is summriz in the fight against socialpestes: An intracuction five crapters and a conclusion and the topic is been addressea and researcledthrought the following screne: An introductory cecaptor that included the conceptual frame work of the study in which the problem and its questions were identified the importance and objectives of the topic were clarified and the terms of the study were identified and the seconacecapteran the essence of the mosque sorigins included a starting with a ristorical overview statement of the merit of its construction and arcritecture in the Hogy Quran them toucrea upon its types importance objectives functions and them revealing its role in building the Islamic community up to its positionisslslam. The second crapteron essence of the mosque starting with a ristorical overview of the mosque's origins included a statement of the merit of its construction and arcritecture in the Holy Qur'an then toucrea upon its types importance objectives functions and them revealingists role in building the lslamic community up to its position in lslam. And in the fourth crapteron the metrocalogicalframework of the study it incrude the fields of study an ecplamtion of the metrod used in the study creatcollectin tools the research community and the sample and then the matrematicalbackgrouna of the study. The fifth crapterceals with the subject in ils field trame work where the results of the field study are presentea and analyzed. In the conclusion of the study we came to same of the most important results: - The mosque is considered the most important rull of the Islamic community as it is a meeting place for Muslims to study their social conditions. -The danger of docug use toan individual's realtr which leads to permanent disability and death. -The results of the study from the students'answers indicate the absence of an effective preventive role an social ills in all its aspects.
مذكرة ماتر تخصص دعوة واعلام
Keywords: المسجد - الآفات الأجتماعية - المخدرات- الفساد الإداري - التمييز العنصري; The mosque - social ills - drugs - administrative corruption - racial discrimination